Interleukin‐4 treatment reduces leukemia burden in acute myeloid leukemia. Issue 5 (26th April 2022) - Qian, Fenghua; Arner, Brooke E.; Kelly, Kathleen M.; Annageldiyev, Charyguly; Sharma, Arati; Claxton, David F.; Paulson, Robert F.; Prabhu, K. Sandeep
Abstract: Interleukin‐4 (IL‐4) is a signature cytokine pivotal in Type 2 helper T cell (Th2) immune response, particularly in allergy and hypersensitivity. Interestingly, IL‐4 increases endogenous levels of prostaglandin D2 (PGD2 ) and its metabolites, Δ 12 ‐prostaglandin J2 (Δ 12 ‐PGJ2 ) and 15‐deoxy‐Δ 12, 14 ‐prostaglandin J2 (15d‐PGJ2 ), collectively called cyclopentenone PGs (CyPGs). However, the therapeutic role of IL‐4 in hematologic malignancies remains unclear. Here, we employed a murine model of acute myeloid leukemia (AML), where human MLL‐AF9 fusion oncoprotein was expressed in hematopoietic progenitor cells, to test the effect of IL‐4 treatment in vivo. Daily intraperitoneal treatment with IL‐4 at 60 µg/kg/d significantly alleviated the severity of AML, as seen by decreased leukemia‐initiating cells (LICs). The effect of IL‐4 was mediated, in part, by the enhanced expression of hematopoietic‐ PGD2 synthase (H‐PGDS) to effect endogenous production of CyPGs, through autocrine and paracrine signaling mechanisms. Similar results were seen with patient‐derived AML cells cultured ex vivo with IL‐4. Use of GW9662, a peroxisome proliferator‐activated receptor gamma (PPARγ) antagonist, suggested endogenous CyPGs‐PPARγ axis mediated p53‐dependent apoptosis of LICs by IL‐4. Taken together, our results reveal a beneficial role of IL‐4 treatment in AML suggesting a potential therapeutic regimen worthy of clinical trials in patients with AML.